PENGARUH PERPUTARAN MODAL KERJA DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN DENGAN PROFITABILITAS SEBAGAI VARIABEL MEDIASI PADA PERUSAHAAN FOOD AND BEVERAGE - Gita Maheswari, I Gusti Ayu; Panji Sedana, Ida Bagus (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.11.NO.06.TAHUN.2022DO - 10.24843/EEB.2022.v11.i06.p08, 2022)
Based on previous research, there are still differences about the factors that influence the company, making them feel interested in conducting deeper. The sample in this study was selected using a purposive sampling technique. Based on the criteria for selecting a sample of 28 population companies, there were 12 companies that met the criteria for selecting the sample. The data analysis technique used was path analysis (path analysis) and t test, F test. Based on the results of the research that has been done, it can be said that: Working capital turnover has a negative and significant effect on firm value in food and beverage companies. The size of the company has no effect on the value of the company in the company's food and beverage. Profitability has a positive and significant effect on company value in food and beverage companies. Working capital turnover has a negative and significant effect on the profitability of food and beverage companies. Company size has a positive and significant effect on the profitability of food and beverage companies. Profitability is able to mediate the effect of working capital turnover on firm value. Profitability is able to mediate the effect of firm size on firm value, where partially firm size has no effect on firm value.